THE INFLUENCE OF ONLINE CUSTOMER REVIEWS AND E-SERVICE QUALITY ON BUYING DECISIONS IN ELECTRONIC COMMERCE - Frans Sudirjo; Ratnawati Ratnawati; Rini Hadiyati; I Nyoman Tri Sutaguna; Muhammad Yusuf (Journal of Management and Creative Business, 2023)
Tokopedia online store has seen a drop in visitors; the drop in online shop visitors at Tokopedia can be interpreted as consumer purchasing decisions at Tokopedia remaining unappealing to the general public, so the Tokopedia online store redoubles its efforts to prevent customers from switching to other online store websites. Requirements for elements that impact purchasing decisions at the Tokopedia online store, such as online customer reviews and the influence of e-services. The purpose of the review is to decide and assess the impact. 1. Determine the impact of an online client survey on purchasing decisions. 2. To determine the impact of e-services on purchasing decisions. 3. To determine the simultaneous impact of online customer reviews and e-service quality on purchasing decisions. Exploration utilizing quantitative methodologies. As many as 278 people participated in the exploratory test. SPSS is used to manage the testing. Given the effect of reviews that online customer reviews influence purchase choices at the Tokopedia online store, e-service quality influences purchase choices at the Tokopedia online store, the concurrent impact of online customer reviews and e-service quality on purchasing decisions at the Tokopedia online store. Tokopedia is an online shopping mall.